Role of neutrophils in type 2 diabetes and associated atherosclerosis. (December 2021) - Keeter, W. Coles; Moriarty, Alina K.; Galkina, Elena V.
Abstract: The development of cardiovascular diseases associated with Type-2 diabetes remains one of the most challenging public health burdens in the developed world. Early onset of metabolic deficiencies, namely dysregulated glucose homeostasis, peripheral insulin resistance, and impaired insulin production are accompanied by both innate and adaptive immune responses that culminate in a state of chronic, low-grade inflammation. Neutrophils are a critical component of the innate immune system which offer frontline defense against pathogens through a variety of potent effector functions. Recent data indicate an essential role of neutrophils in various disease processes that contribute to the development of Type-2 diabetes and atherosclerosis. In this brief review, we aim to distill the most relevant clinical and pre-clinical literature that investigates the role of neutrophils as an important mediator for the Type-2 diabetes/atherosclerosis connection. Highlights: Neutrophils directly contribute to atherosclerotic plaque formation and destabilization. Neutrophils support recruitment of leukocytes to atherosclerosis-prone sites. Neutrophil-to-lymphocyte ratio is a common characteristic of type-2 diabetes and predicts disease progression. Neutrophils contribute to peripheral insulin resistance via adipose tissue inflammation. Neutrophils progress atherosclerosis and Type-2 diabetes via reactive oxygen species and neutrophil extracellular trap production.